Police Discretion in the Management of Public Demonstrations: Evidence from the Sragen Police Department - Supriyanto, Supriyanto; Faried, Femmy Silaswati; Suniaprily, Firstnandiar Glica Aini (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Police discretionary authority constitutes a strategic legal instrument for maintaining public order, particularly in managing demonstrations with the potential to disrupt security. Nevertheless, the exercise of discretion may give rise to legal concerns if it is not carried out in accordance with the principles of legality, justice, and the protection of human rights. This study examines the implementation of discretionary authority by the Sragen Police within the framework of applicable laws and regulations and evaluates its conformity with the principles of justice, due process of law, and respect for human rights. Employing a normative–empirical legal methodology, this study adopts statutory, conceptual, and case-based approaches, supported by field data obtained through interviews and a review of relevant literature. The findings indicate that police discretion in Sragen has generally been exercised in a proportional and accountable manner, consistent with the prevailing legal framework and with an emphasis on preventive measures. The study concludes that police discretion functions effectively as an adaptive legal instrument insofar as it remains bounded by legal accountability and professional ethics.